Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis

Platinum-free electrocatalysts based on electrodeposited Co-Mn-Ni alloys for efficient electrocatalytic alkaline water splitting - Chandran, M. Athira; Dutta, Pritha; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (ACS Applied Energy Materials, 2025)
The development of a Pt-free electrocatalyst for efficient and stable water splitting is crucial for the commercialization of green hydrogen production. A low-cost electrocatalyst with good hydrogen and oxygen evolution activities (HER and OER, respectively) displaying long durability is the first step in this direction, and if the catalyst can be synthesized via an easy, convenient, and scalable procedure, that would be an added advantage. Multicomponent alloys, with their tunable compositions and abundant active sites, present a promising solution in this direction. Herein, a cost-effective CoMnNi (CMN) alloy is synthesized via electrodeposition and with optimized composition by tuning the electrolyte concentration and deposition potential to enhance electrocatalytic performance. The resulting single-phase alloy exhibits a high electrochemical surface area with an average particle size of similar to 4 nm, demonstrating excellent hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities in 1 M KOH, with overpotentials of 121 mV at -10 mA cm-2 and 285 mV at 20 mA cm-2, respectively. Moreover, the catalyst exhibits remarkable stability, sustaining 100 h of operation at 100 mA cm-2. The CMN alloy also performs efficiently under harsh conditions, including 6 M KOH and alkaline seawater, in both symmetric and asymmetric cell configurations. This work highlights the potential of multicomponent alloys as durable, high-performance electrocatalysts for scalable water splitting, paving the way for sustainable hydrogen production.
Keywords: alkaline seawater; electrocatalysis; Electrodeposition; hydrogen evolution reaction(HER); multicomponentalloy; oxygen evolution reaction (OER); stability; watersplitting